Small is beautiful a study of economics as if people mattered - Schumacher, E. F (London Blond and Briggs, 1973)
Small is Beautiful is E. F. Schumacher's stimulating and controversial study of economics and its purpose. This remarkable book examines our modern economic system - its use of resources and impact on how we live - questioning whether they reflect what we truly care about. The revolutionary ideas are as pertinent, inspirational and thought-provoking today as when they were first published in 1973.
Includes bibliographical references.
Keywords: Economics